2018
DOI: 10.2319/111617-792.1
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary arch dimensions associated with acoustic parameters in prepubertal children

Abstract: There is a significant association between arch dimensions, particularly arch length and depth, and voice parameters. The formant most predictive of arch depth and width is the third formant, along with fundamental frequency of voice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The current study reported that unilateral and bilateral impacted maxillary canine groups had considerably smaller IMW, IPW, ICW, and AL than the control group. These findings were consistent with other reports, which reported that the impacted maxillary canine group had a shorter and narrower maxillary arch than the control group [40,44].…”
Section: Discussionsupporting
confidence: 93%
“…The current study reported that unilateral and bilateral impacted maxillary canine groups had considerably smaller IMW, IPW, ICW, and AL than the control group. These findings were consistent with other reports, which reported that the impacted maxillary canine group had a shorter and narrower maxillary arch than the control group [40,44].…”
Section: Discussionsupporting
confidence: 93%